Investigation of the electrical characteristics of commercial diodes under mixed-radiation - Hasbullah, Nurul Fadzlin; Alang Md Rashid, Nahrul Khair (s.n, 2012)
Changes to electrical (I-V and C-V) characteristics of diodes may also be modified due to application in extreme radiation environment. Silicon (Si) and Gallium Arsenide (GaAs) commercial diodes were irradiated at low and high dose neutron radiatin. Current-voltage (I-V) measurements at low dose irradiation show a decrease in forward (FB) and reverse bias (RB) leakage current of both Si diodes